(untitled) (Journal of Applied Oral Science, 2022)
Background: Osteoradionecrosis of the jaw (ORNJ) is the most severe and complex sequel of head and neck radiotherapy (RT) because of the bone involved, it may cause pain, paresthesia, foul odor, fistulae with suppuration, need for extra oral communication and pathological fracture. We treated twenty lesions of ORNJ using low-level laser therapy (LLLT) and antimicrobial photodynamic therapy (aPDT). The objective of this study was to stimulate the affected area to homeostasis and to promote the healing of the oral mucosa. Methods: We performed aPDT on the exposed bone, while LLLT was performed around the bone exposure (red spectrum) and on the affected jaw (infrared spectrum). Monitoring and clinical intervention occurred weekly or biweekly for 2 years. Results: 100% of the sample presented clinical improvement, and 80% presented complete covering of the bone exposure by intact oral mucosa. Conclusion:LLLT and aPDT showed positive results as an adjuvant therapy to treat ORNJ.